Dual asymmetric centrifugation as a novel method to prepare highly concentrated dispersions of PEG-b-PCL polymersomes as drug carriers - Köthe, Tobias; Martin, Stefan; Reich, Gabriele; Fricker, Gert (International journal of pharmaceutics, 2020)
Polymersomes are vesicles formed by self-assembly from block copolymers. A widely studied biodegradable diblock copolymer that forms polymersomes is poly(ethylene-glycol)-block-poly(ε-caprolactone) (PEG-b-PCL). Polymersomes from this copolymer have been prepared by various methods. Major drawbacks are either the use of organic solvents, the need for post-preparation steps or low polymer concentration in resulting dispersions. Here, we studied the use of dual asymmetric centrifugation (DAC) as alternative and innovative preparation method by which these disadvantages can be overcome. We investigated the influence of process parameters on the size of resulting particles and their morphology. Additionally, the ability of this method to encapsulate both hydrophilic and hydrophobic drugs into polymersomes was assessed to evaluate its usefulness in the manufacture of nano-therapeutics. We found, that depending on process parameters, formation of nanosized vesicles with considerable drug encapsulation is achievable. Interestingly, with DAC polymersomes could also be prepared from a high molecular weight copolymer that was not able to generate vesicles by conventional methods. In addition, no organic solvents are used, no postprocessing is necessary and preparation is done quickly in a single vessel, minimizing product loss. DAC leads to highly concentrated, drug-loaded polymersome dispersions and therefore represents a major step towards their applicability in nanomedicine.
Gesehen am 12.06.2020